Respuesta :

Answer:

-8

Step-by-step explanation:

Distribute.

-8x - 12 = 2x + 6 - 8x - 2

Combine like terms.

2x = -16

Divide by 2 on both sides

x = -8

Answer:

The solutions of given equations is x = -8

Step-by-step explanation:

It is given that,

-4(2x + 3) = 2x + 6 - (8x + 2)

To find the solution of given equation

-4(2x + 3) = 2x + 6 - (8x + 2)

-8x - 12 = 2x + 6 - 8x - 2

-8x - 12 = 4 - 6x

-8x + 6x = 4 + 12

-2x = 16

x = 16/(-2) = -8

Therefore the solutions of given equations is x = -8

ACCESS MORE